PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Kasus Pada Sektor Manufaktur Periode Tahun 2003 â 2007) - Asoka Sakti, Tutus Alun (STIE Totalwin Semarang, 2010)
Investor always hoping to get return in their investation of stock. Purpose of this research is to analyse independent variable that consist of return asset on and debt to equity ratio manufacturing company listed of Indonesia Stock Exchange (IDX). Sample of this research is 113 manufacturing company in IDX with method purposive non random sampling. This research used multiple regression test is done by normality test, variation test of classic assumption (multikolinearity, heteroskedastisity and autocorrelation), hypothesis test ( t and F) and test coefficient of determination. The result of this research that return on asset have positive influence and doesnt signifikan to stock return listing manufacturing campany of Indonesia Stock Exchange. Debt to equity ratio has negatif influence signifikan to stock return manufacturing company listing of Indonesia Stock Exchange